2015
DOI: 10.1371/journal.pone.0130161
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Trends of the Transposase-Encoding Open Reading Frames A and B (orfA and orfB) of the Mycobacterial IS6110 Insertion Sequence

Abstract: BackgroundThe IS6110 insertion sequence, a member of the IS3 family of insertion sequences, was found to be specific to the Mycobacterium tuberculosis complex (MTBC). Although IS6110 has been extensively characterized as a transposable genetic marker, the evolutionary history of its own transposase-encoding sequence has not, to the best of our knowledge, been investigated.Methodology/Principal FindingsHere we explored the evolution of the IS6110 sequence by analysing the genetic variability and the selective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 76 publications
1
7
1
Order By: Relevance
“…In addition, two other mutations are in the IR, which we do not expect to be involved in the transposase function as they are outside the coding region. Thabet et al (2015) also found more polymorphic sites for orfB than for orfA. They suggested that non-synonymous mutations tend to be eliminated because the ancestral IS6110 copy inherited by the MTBC would be functionally optimal.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In addition, two other mutations are in the IR, which we do not expect to be involved in the transposase function as they are outside the coding region. Thabet et al (2015) also found more polymorphic sites for orfB than for orfA. They suggested that non-synonymous mutations tend to be eliminated because the ancestral IS6110 copy inherited by the MTBC would be functionally optimal.…”
Section: Discussionmentioning
confidence: 97%
“…IS 6110 has been used for a long time for diagnosis and genotyping, but very little is known about its genetic variability, mainly due to the difficulties in determining its complete sequence for each copy location in the genome. The limited data that have been published regarding this issue have shown dissimilar results ( Dale et al, 1997 ; Thabet et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations